Analysis of new mutant and hybrid amaranth samples by main economic traits in the conditions of the Eastern Forest-Steppe of Ukraine (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
The limited breeding material of amaranth in Ukraine significantly hinders the development of high-yielding varieties. Most of the available genotypes do not fully meet modern breeding requirements, which complicates the obtaining of new promising forms with a complex of valuable economic traits. Purpose. The aim of the study was a comprehensive breeding characterization of new amaranth samples of mutant and hybrid origin according to key valuable economic traits under the conditions of the Eastern Forest-Steppe of Ukraine in order to identify promising source material. Methods. The objects of the study were 11 breeding samples obtained on the basis of the Ultra and Kharkivskyi 1 varieties by chemical mutagenesis (treatment with dimethyl sulfate, diethyl sulfate, and ethyl methanesulfonate) followed by selections in mutant and hybrid populations. The research was conducted in 2024–2025 under field conditions on typical chernozem using the randomized block design in three replications. The duration of the vegetation period, plant height, panicle length, productivity per plant, and 1000-seed weight were evaluated. Statistical data processing was performed using variation analysis, one-way analysis of variance, cluster analysis, and biplot analysis. Results. The vegetation period ranged from 90 to 132 days. Cluster analysis clearly identified three maturity groups: early-maturing (samples №6, №7, №12 — 90–99 days), mid-maturing (№2, №4, №5, №10, №11, № 220 – 100–115 days), and late-maturing (№52, №106 – 120–132 days). Plant height varied from 61.7 to 131.7 cm. Most samples fell within the optimal range. The tallest were samples №10 (128.0–131.7 cm), №6 (121.0–130.0 cm), and №7 (125.0–129.7 cm); the shortest were №220 (61.7–63.3 cm) and №52 (72.0–76.3 cm). Panicle length ranged from 10.0 to 35.0 cm, with maximum values in samples №10 (33.3–34.7 cm), №7 (33.0–34.3 cm), №2 (30.7–35.0 cm), and №6 (30.3–33.0 cm). Productivity per plant varied from 2.4 to 10.7 g, with the highest values recorded for sample №106 (9.0–10.7 g), as well as №10 (8.1–8.6 g) and №2 (7.8–8.1 g). The 1000-seed weight was in the range of 480–870 g, with the highest values in samples №12 (750–870 g), №52 (750–830 g), and №220 (700–760 g). Biplot analysis of the complex of traits revealed the most valuable group of samples (№10, №6, №7, №2, №5, №11), which combines a well-developed panicle and high productivity. Sample №106 stood out as a source of high productivity (average 9.85 g per plant). Samples №52, №220, and №12 were characterized by increased 1000-seed weight but were inferior in panicle length and overall productivity. Conclusions. As a result of the study, promising breeding samples of amaranth with optimal plant height, different maturity groups, and high productivity were identified. Practical value of the work lies in the creation of new genetic material suitable for use in breeding programs aimed at developing high-yielding, technologically advanced amaranth varieties adapted to the conditions of the Eastern Forest-Steppe of Ukraine.
Keywords: amaranth; amaranth breeding; chemical mutagenesis; mutant lines; hybrid populations; economic traits; vegetation period; plant productivity; biplot analysis; breeding material